Effects of S-metolachlor and its degradation product metolachlor OA on marbled crayfish (Procambarus virginalis) - Stara, Alzbeta; Kubec, Jan; Zuskova, Eliska; Buric, Milos; Faggio, Caterina; Kouba, Antonin; Velisek, Josef (Chemosphere, 2019)
Increasing production of energy crops in Europe, mainly maize and rapeseed, has altered patterns of pesticide use in recent decades. The long-term effects of S-metolachlor (S-M) and of its metabolite metolachlor OA (M-OA) at the environmentally relevant concentration of 4.2 μg L-1 and at 42 μg L-1 (ten-fold concentration) on marbled crayfish (Procambarus virginalis) were evaluated in a 28-day exposure and after a subsequent 28-day recovery period. Indicators assessed were behaviour; biochemical haemolymph profile; oxidative and antioxidant parameters of gill, hepatopancreas, and muscle; and histology of hepatopancreas and gill. Results showed biochemical haemolymph profile (lactate, alanine aminotransferase, aspartate aminotransferase, inorganic phosphate), lipid peroxidation in hepatopancreas, and antioxidant parameters (catalase, reduced glutathione, glutathione S-transferase) of hepatopancreas and gill of crayfish exposed to S-M and M-OA to significantly differ from controls (P < 0.01). Antioxidant biomarker levels remained different from controls after a 28-day recovery period. Differences in behaviour including speed of movement and velocity, and histopathological damage to gill and hepatopancreas were associated with S-M and M-OA exposure and persisted after 28 days in S-M- and M-OA-free water. Results suggest harmful effects of low concentrations of S-M and its metabolite M-OA on non-target organisms and provide information for assessing their effects at environmentally relevant concentrations.
Keywords: Recovery; Histology; Europe; hemolymfa; Antioxidants; chování zvířat; Hemolymph; Evropa; Crustacean; Herbicide; Animals; Biomarkers; hepatopankreas; severní raci; Lipid Peroxidation; antioxidancia; zvířata; Metabolite; peroxidace lipidů; Astacoidea; Behavior, Animal; Hepatopancreas; Acetamides; acetamidy